"Nivel de conocimiento sobre alimentación y estado nutricional en pacientes con enfermedad renal crónica" - Quiliche Chávez, Anai Caroline (2016)
This research quantitative, descriptive and correlational was perfomed during the months of January – February 2015, the hospital Lazarte from Trujillo, was designed to determine the relationship between know about alimentation level and the nutrition state of the patient with Chronic Kidney Disease. The sample was perfomed of 76 patients, for data colletion using one instruments: “test to assess the know of alimentation patients with chronic kidney disease”. The results sample: the 68 percent of patients with Chronic Kidney Disease presented a level regular of know about alimentation, the 29 percent, level good of know and the 3 percent, level low of know about alimentation; the 45 percent of patients with Chronic Kidney Disease have normal nutritional status, the 39 percent have sobrepeso, the 16 percent are obese and none morbidly obese present. Significant relationship between the nutrition state and know about alimentation level of the patient with Chronic Kidney Disease.